Long-term monitoring of aspen forest regeneration and ungulate use shows successful recruitment amid landscape-scale forest restoration - Sterling B. Kerr; Aaron C. Rhodes; April Hulet; Ryan Pienaar; Samuel B. St. Clair (Forest Ecology and Management, 2026)

Controls of sea–air O2 and CO2 exchanges along the Patagonian shelf-break: the role of temperature and phytoplankton communities - Luísa M. Garcia; Iole Beatriz M. Orselli; Virginia Maria Tavano; Carlos Rafael B. Mendes; Carlos Alberto E. Garcia; Rosane G. Ito; Catherine Goyet; Rodrigo Kerr (Progress in Oceanography, 2026)

Apicomplexan and non-metazoan microeukaryotes in the thermosensitive reef-building coral Acropora hyacinthus shift in abundance throughout an extreme coral bleaching event - Athena Peterson; Sunni Patton; Emily R. Schmeltzer; Carsten G. B. Grupstra; Lauren I. Howe-Kerr; J. Grace Klinges; Rebecca L. Maher; Adriana Messyasz; Sarah Seabrook; Andrew R. Thurber; Adrienne M. S. Correa; Rebecca L. Vega Thurber (Frontiers in Marine Science, 2025)
Coral reefs play vital roles in global marine systems and are currently facing increased threats of bleaching. Coral bleaching is heavily influenced by the host-associated microeukaryote community – most notably the dinoflagellate family Symbiodiniaceae. The apicomplexan family Corallicolidae, is the second most abundant member of the microeukaryote community, yet their role in coral health is largely unknown. To explore the role that this apicomplexan and the greater non-metazoan microeukaryotic community play in coral health, samples of a thermally sensitive scleractinian coral, Acropora hyacinthus , were collected over the course of a severe coral bleaching event and its aftermath. Through 18S rRNA gene sequencing analysis, we found that taxa within the family Corallicolidae were relatively enriched in corals during, and immediately after, the severe bleaching event as compared to before or one year after. Although utilizing 18S rRNA gene sequencing methods is not the standard for Symbiodiniaceae community profiling, we were able to observe symbiont shuffling among the Symbiodiniaceae communities, as the dominant algal symbiont shifted from the genus Cladocopium to the genus Symbiodinium following the bleaching event. Furthermore, the non-metazoan microeukaryote community displayed a general shift towards a state of dysbiosis; evidenced by substantial changes in both microeukaryote community composition and dispersion. These results offer insight into the dynamics of apicomplexans throughout the course of an increasingly common global coral reef stressor.

Effect of packaging and storage temperature on shelled pecan chemical quality indicators and their impact on consumer acceptance - Vivian E. Yang; William L. Kerr; Ronald B. Pegg; Adrian L. Kerrihard (Food Packaging and Shelf Life, 2025)

Spatial and Temporal Heterogeneity of Fish Spawning Dynamics on the West Florida Shelf During Fall - Keith Keel; Makenzie Kerr; Laura Y. Liu; Yonggang Liu; Joshua P. Kilborn; Glenn Zapfe; Ernst B. Peebles; Christopher D. Stallings; Mya Breitbart (Fisheries Oceanography, 2025)
Identifying spawning areas for economically and ecologically important fishes is critical for fisheries conservation and ecosystem‐based management. We used genetic barcoding to identify fish eggs collected across the West Florida Shelf (WFS) during September of 2013, 2014, and 2019. Fish eggs were collected on Southeast Area Monitoring and Assessment Program (SEAMAP) ichthyoplankton cruises using a Continuous Underway Fish Egg Sampler. Analysis of 4833 fish eggs from the 3 years resulted in the identification of 82 species within 35 families. A 78% DNA barcoding success rate was achieved, with 46% of all identifications being at the species level. PERMANOVA results revealed significant differences in fish egg beta‐diversity across time (the 3 years sampled) and space (preassigned levels of both depth class and regional strata). Our findings generally aligned with known adult fish distributions and spawning patterns, and we found that water‐column depth played a more important role than regional strata in structuring the fish egg assemblages. Eggs from several economically important species were collected and observed at relatively high frequencies, including red snapper, lane snapper, vermilion snapper, yellowedge grouper, and king mackerel. We used the West Florida Coastal Ocean Model to hindcast the trajectories of all fish eggs and trace them back to possible spawning locations. We conducted backward tracking over a span of 36 h based on the assumption that most fish eggs on the WFS undergo hatching within this time window. The model estimated egg transport distances ranging from 1 to 79 km (mean distance of ~21 km), with greater transport distances estimated on the outer shelf in comparison to the middle and inner shelf. These results further our understanding of the spatial and interannual variation of fish spawning dynamics on the WFS and mark the beginning of a long‐term monitoring effort.

Effects of packaging and storage temperature on shelled pecan quality - Vivian E. Yang; William L. Kerr; Ronald B. Pegg; Adrian L. Kerrihard (Postharvest Biology and Technology, 2025)

Increased BMI is associated with an altered decision-making process during healthy food choices in males and females - Larenas G; Luarte L; Kerr B; Ossandón T; Cortés V; Baudrand R; Pérez Leighton C (Appetite, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

5-HT2C agonism as a neurotherapeutic for sarcopenia: preclinical proof of concept - Nathan R. Kerr; Anna R. Dashtmian; Fereshteh B. Darvishi; Charles D. Brennan; Sindhuja N. Ayyagari; Peter J. Moore; Jose A. Viteri; Meifang Wang; Mark M. Rich; Brian C. Clark; W. David Arnold (GeroScience, 2025)

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Metabolomic analysis combined with machine learning algorithms enables the evaluation of postharvest pecan color stability - Min Jeong Kang; Ronald B. Pegg; William L. Kerr; M. Lenny Wells; Patrick J. Conner; Joon Hyuk Suh (Food Chemistry, 2024)

Sea-air CO2 exchanges, pCO2 drivers and phytoplankton communities in the southwestern South Atlantic Ocean during spring - Rodrigo Kerr; Thiago Monteiro; Iole Beatriz M. Orselli; Virginia Maria Tavano; Carlos Rafael B. Mendes (Marine Chemistry, 2024)

Statistical modelling of sensory, physical, and chemical changes in almonds during prolonged storage at different conditions: Effect of shelling on shelf life - Daniel P. Seeler; William L. Kerr; Adrian L. Kerrihard; George A. Cavender; Guangwei Huang; Ronald B. Pegg (Postharvest Biology and Technology, 2024)

Retention and export of planktonic fish eggs in the northeastern Gulf of Mexico - Bich Vi Viviane Nguyen; Yonggang Liu; Christopher D. Stallings; Mya Breitbart; Steven A. Murawski; Robert H. Weisberg; Makenzie Kerr; Eva‐Maria S. Bønnelycke; Ernst B. Peebles (Fisheries Oceanography, 2024)
To help determine whether planktonic eggs of fishes on the West Florida Shelf (WFS) are retained locally or exported elsewhere, we collected fish eggs by plankton net from 17 locations (stations) and identified them using DNA barcoding. We then entered the station coordinates into the West Florida Coastal Ocean Model (WFCOM) and simulated the trajectories of the passively drifting eggs over 2 weeks at three depths (surface, midwater, and near bottom). The results indicated there were two groups of trajectories: a nearshore group that tended to be retained and an offshore group that tended toward export and potential long‐distance dispersal. We also found evidence of a relationship between retention and higher fish‐egg abundance; nearshore stations were associated with higher fish‐egg abundances and higher retention. We suggest this is the result of (1) increased spawning in high‐retention areas, (2) increased drift convergence in high‐retention areas, or both processes acting together. Community analysis using SIMPROF indicated the presence of a depth‐related (retention‐related) difference in species assemblages. Fish‐egg species were also categorized as pelagics or non‐pelagics; there was no evidence of pelagic species being more likely to be exported.

Seasonal variability in water‒air CO2 exchanges and carbon origin in a subtropical estuary - Cíntia Albuquerque; Rodrigo Kerr; Thiago Monteiro; Andréa da Consolação de Oliveira Carvalho; Eunice da Costa Machado; Carlos Rafael B. Mendes (Estuarine, Coastal and Shelf Science, 2023)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Physical-biological drivers modulating phytoplankton seasonal succession along the Northern Antarctic Peninsula - Raul Rodrigo Costa; Afonso Ferreira; Márcio S. de Souza; Virginia M. Tavano; Rodrigo Kerr; Eduardo R. Secchi; Vanda Brotas; Tiago S. Dotto; Ana C. Brito; Carlos Rafael B. Mendes (Environmental Research, 2023)

Consequences of ignoring climate impacts on New England groundfish stock assessment and management - Mackenzie D. Mazur; Jerelle Jesse; Steven X. Cadrin; Samuel B. Truesdell; Lisa Kerr (Fisheries Research, 2023)

Consumer feces impact coral health in guild-specific ways - Carsten G. B. Grupstra; Lauren I. Howe-Kerr; Jesse A. van der Meulen; Alex J. Veglia; Samantha R. Coy; Adrienne M. S. Correa (Frontiers in Marine Science, 2023)
Animal waste products are an important component of nutrient cycles and result in the trophic transmission of diverse microorganisms. There is growing recognition that the feces of consumers, such as predators, may impact resource species, their prey, via physical effects and/or microbial activity. We tested the effect of feces from distinct fish trophic groups on coral health and used heat-killed fecal controls to tease apart physical versus microbial effects of contact with fecal material. Fresh grazer/detritivore fish feces caused lesions more frequently on corals, and lesions were 4.2-fold larger than those from sterilized grazer/detritivore feces; in contrast, fresh corallivore feces did not cause more frequent or larger lesions than sterilized corallivore feces. Thus, microbial activity in grazer/detritivore feces, but not corallivore feces, was harmful to corals. Characterization of bacterial diversity in feces of 10 reef fish species, ranging from obligate corallivores to grazer/detritivores, indicated that our experimental findings may be broadly generalizable to consumer guild, since feces of some obligate corallivores contained ~2-fold higher relative abundances of coral mutualist bacteria ( e.g., Endozoicomonadaceae), and lower abundances of the coral pathogen, Vibrio coralliilyticus , than feces of some grazer/detritivores. These findings recontextualize the ecological roles of consumers on coral reefs: although grazer/detritivores support coral reef health in various ways ( e.g. , promoting coral settlement and herbivory through the removal of detritus and sediments from the algal matrix), they also disperse coral pathogens. Corallivore predation can wound corals, yet their feces contain potentially beneficial coral-associated bacteria, supporting the hypothesized role of consumers, and corallivores in particular, in coral symbiont dispersal. Such consumer-mediated microbial dispersal as demonstrated here has broad implications for environmental management.

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Changes in Phytoplankton Communities Along the Northern Antarctic Peninsula: Causes, Impacts and Research Priorities - Afonso Ferreira; Raul R. Costa; Tiago S. Dotto; Rodrigo Kerr; Virginia M. Tavano; Ana C. Brito; Vanda Brotas; Eduardo R. Secchi; Carlos R. B. Mendes (Frontiers in Marine Science, 2020)

Developmental trap or demographic bonanza? Opposing consequences of earlier phenology in a changing climate for a multivoltine butterfly - Natalie Z. Kerr; Tyson Wepprich; Fritzi S. Grevstad; Erik B. Dopman; Frances S. Chew; Elizabeth E. Crone (Global Change Biology, 2020)
A rapidly changing climate has the potential to interfere with the timing of environmental cues that ectothermic organisms rely on to initiate and regulate life history events. Short‐lived ectotherms that exhibit plasticity in their life history could increase the number of generations per year under warming climate. If many individuals successfully complete an additional generation, the population experiences an additional opportunity to grow, and a warming climate could lead to a demographic bonanza. However, these plastic responses could become maladaptive in temperate regions, where a warmer climate could trigger a developmental pathway that cannot be completed within the growing season, referred to as a developmental trap. Here we incorporated detailed demography into commonly used photothermal models to evaluate these demographic consequences of phenological shifts due to a warming climate on the formerly widespread, multivoltine butterfly ( Pieris oleracea ). Using species‐specific temperature‐ and photoperiod‐sensitive vital rates, we estimated the number of generations per year and population growth rate over the set of climate conditions experienced during the past 38 years. We predicted that populations in the southern portion of its range have added a fourth generation in recent years, resulting in higher annual population growth rates (demographic bonanzas). We predicted that populations in the Northeast United States have experienced developmental traps, where increases in the thermal window initially caused mortality of the final generation and reduced growth rates. These populations may recover if more growing degree days are added to the year. Our framework for incorporating detailed demography into commonly used photothermal models demonstrates the importance of using both demography and phenology to predict consequences of phenological shifts.

Acute toxicity testing of TiO2-based vs. oxybenzone-based sunscreens on clownfish (Amphiprion ocellaris) - Alexandra N. Barone; Caitlyn E. Hayes; James J. Kerr; Ryan C. Lee; Denise B. Flaherty (Environmental Science and Pollution Research, 2019)

Quantifying the thermal tolerance of wood borers and bark beetles for the development of Joule heating as a novel phytosanitary treatment of pine logs - S. M. Pawson; M. K.-F. Bader; E. G. Brockerhoff; W. J. B. Heffernan; J. L. Kerr; B. O’Connor (Journal of Pest Science, 2019)

Assessment of in silico protein sequence analysis in the clinical classification of variants in cancer risk genes - Iain D. Kerr; Hannah C. Cox; Kelsey Moyes; Brent Evans; Brianna C. Burdett; Aric van Kan; Heather McElroy; Paris J. Vail; Krystal L. Brown; Dechie B. Sumampong; Nicholas J. Monteferrante; Kennedy L. Hardman; et al. (Journal of Community Genetics, 2017)

A new eimerian (Apicomplexa: Eimeriidae), from ornate box turtle, Terrapene ornata (Agassiz) (Testudines: Emydidae) from northwest Arkansas, USA - Chris T. McAllister; Dagmara Motriuk-Smith; Catherine M. Kerr; Kristine N. Carmen; R. Scott Seville; Matthew B. Connior (Systematic Parasitology, 2017)

A review of 15 years of Spartina management in the San Francisco Estuary - Drew W. Kerr; Ingrid B. Hogle; Brian S. Ort; Whitney J. Thornton (Biological Invasions, 2016)

The Western South Atlantic Ocean in a High-CO2 World: Current Measurement Capabilities and Perspectives - Rodrigo Kerr; Letícia C. da Cunha; Ruy K. P. Kikuchi; Paulo A. Horta; Rosane G. Ito; Marius N. Müller; Iole B. M. Orselli; Jannine M. Lencina-Avila; Manoela R. de Orte; Laura Sordo; Bárbara R. Pinheiro; Frédéric K. Bonou; et al. (Environmental Management, 2016)

Remote Sensing of Water Resources in Semi-Arid Mediterranean Areas: the joint international laboratory TREMA - L. Jarlan; S. Khabba; S. Er-Raki; M. Le Page; L. Hanich; Y. Fakir; O. Merlin; S. Mangiarotti; S. Gascoin; J. Ezzahar; M.H. Kharrou; B. Berjamy; et al. (International Journal of Remote Sensing, 2015)

Coral reef recovery in the Galápagos Islands: the northernmost islands (Darwin and Wenman) - Peter W. Glynn; Bernhard Riegl; Samuel Purkis; Jeremy M. Kerr; Tyler B. Smith (Coral Reefs, 2015)

Topographical variation reduces phenological mismatch between a butterfly and its nectar source - B. J. Hindle; C. L. Kerr; S. A. Richards; S. G. Willis (Journal of Insect Conservation, 2015)

Larval dispersal and population connectivity among a network of marine reserves - Brandon J. Puckett; David B. Eggleston; Patrick C. Kerr; Richard A. Luettich (Fisheries Oceanography, 2014)
A major challenge in marine ecology is describing patterns of larval dispersal and population connectivity, as well as their underlying processes. We used a biophysical model to simulate dispersal of eastern oyster, Crassostrea virginica , larvae and connectivity among a network of 10 no‐take reserves in a shallow, wind‐driven estuary to assess the relative importance of spawning location, spawning date, larval behavior, larval mortality, and adult reproductive output to predicted dispersal and connectivity patterns. The location (i.e., natal reserve) and date of spawning relative to physical processes, particularly frequency of wind reversals, were the dominant drivers of dispersal and connectivity patterns. To a lesser extent, larval behavior (i.e., 3D vertical advection and ontogenetic depth regulation) and mortality modified dispersal and connectivity, whereas spatiotemporal variability in adult reproductive output was of minimal importance. Over a 21‐day larval duration, mean dispersal distance of passive surface particles ranged from 5 to 40 km. Reserves were too small (1 km 2 ) relative to mean dispersal distances to promote extensive local retention (median 2%) and spaced too far apart (typically ~50 km) to promote extensive inter‐reserve connectivity (median 2%). Limited connectivity and local retention may preclude the network from being self‐sustainable, thereby limiting its long‐term conservation and management benefits. In reserve systems characterized by limited connectivity, management efforts should focus on increasing connectivity by increasing the number or size of reserves to realize the benefits of improved adult demographics within reserves.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Persistent Increase of Blood Lead Level and Suppression of δ-ALAD Activity in Northern Bobwhite Quail Orally Dosed With Even a Single 2-mm Spent Lead Shot - S. D. Holladay; R. Kerr; J. P. Holladay; B. Meldrum; S. M. Williams; R. M. Gogal (Archives of Environmental Contamination and Toxicology, 2012)

Modelling experimental uveitis: barrier effects in autoimmune disease - David Nicholson; Emma C. Kerr; Owen G. Jepps; Lindsay B. Nicholson (Inflammation Research, 2012)

Oral and Pharyngeal Cancer Control and Early Detection - Sol Silverman; A. Ross Kerr; Joel B. Epstein (Journal of Cancer Education, 2010)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Simultaneous freeze tolerance and avoidance in individual fungus gnats, Exechia nugatoria - Todd Sformo; F. Kohl; J. McIntyre; P. Kerr; J. G. Duman; B. M. Barnes (Journal of Comparative Physiology B, 2009)

Stingless Bees: Chemical Differences and Potential Functions in Nannotrigona testaceicornis and Plebeia droryana Males and Workers - Adriana Pianaro; Cristiano Menezes; Warwick Estevam Kerr; Rodrigo B. Singer; Eda Flávia Lotufo R. A. Patricio; Anita J. Marsaioli (Journal of Chemical Ecology, 2009)

A New Prokaryotic Farnesyldiphosphate Synthase from the Octocoral Eunicea Fusca: Differential Display, Inverse PCR, Cloning, and Characterization - Llanie K. Ranzer; Thomas B. Brück; Wolfram M. Brück; Jose V. Lopez; Russell G. Kerr (Marine Biotechnology, 2009)

Diversity of the Bacterial Communities Associated with the Azooxanthellate Deep Water Octocorals Leptogorgia minimata, Iciligorgia schrammi, and Swiftia exertia - Thomas B. Brück; Wolfram M. Brück; Lory Z. Santiago-Vázquez; Peter J. McCarthy; Russell G. Kerr (Marine Biotechnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Pollination by Sexual Mimicry in Mormolyca ringens: A Floral Chemistry that Remarkably Matches the Pheromones of Virgin Queens of Scaptotrigona sp. - Adriana Flach; Anita J. Marsaioli; Rodrigo B. Singer; Maria Do Carmo E. Amaral; Cristiano Menezes; Warwick Estevam Kerr; Luciane G. Batista-Pereira; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)

Sequence mapping of the Californian MSW strain of Myxoma virus - A. Labudovic; H. Perkins; B. van Leeuwen; P. Kerr (Archives of Virology, 2004)

Trade-offs and coexistence in microbial microcosms - Brendan J.M. Bohannan; Ben Kerr; Christine M. Jessup; Jennifer B. Hughes; Gunnar Sandvik (Antonie van Leeuwenhoek, 2002)

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Slant Column Measurements of O3 and NO2 During the NDSC Intercomparison of Zenith-Sky UV-Visible Spectrometers in June 1996 - H. K. Roscoe; P. V. Johnston; M. Van Roozendael; A. Richter; A. Sarkissian; J. Roscoe; K. E. Preston; J-C. Lambert; C. Hermans; W. DeCuyper; S. Dzienus; T. Winterrath; et al. (Journal of Atmospheric Chemistry, 1999)